Transmediastinal Gunshot Wound in a Pregnant Patient with Stable Hemodynamics - Ozdemır, Ozhan; Atalay, Cemal Resat (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Transmediastinal gunshot wounds (TGWs) may lead to life-threatening injuries of vital organs such as large vessels, the esophagus, and lungs. Although they are not commonly encountered in pregnant women, additional caution should be given to these patients. Physical examination for the diagnosis and the choice of treatment modality contain controversial points in hemodynamically stable patients, and resuscitation has excessive importance due to physiological changes in pregnancy. We present a hemodynamically stable 26-week pregnant woman brought to the emergency department for TGW. She had a 1-cm diameter of bullet entrance hole on the right anterior 4th intercostal space, 2 cm lateral to the sternum, and a 3-cm diameter exit hole on the right posterior 12th intercostal space on the midscapular line. With our conservative approach, she had an uncomplicated pregnancy period, and gave birth to a healthy baby at term.
Keywords: gunshot; transmediastinal; trauma; pregnancy